Application of QUAL2Kw for Water Quality Modeling in the Tunggak River, Kuantan, Pahang, Malaysia - Hossain, Mohamed Amjed; Islam, Mir Sujaul; Nasly, Mohamed Ali (International Science Congress Association, 2014)
The Tunggak River receives waste water from the Gebeng industrial estate (GIE) and from some agricultural and homestead areas in Kuantan, Malaysia. Discharges of industrial effluents containing conventional and non-conventional pollutant with degradable organics and nutrients are the major cause of water quality deterioration in this river. Degradable organic and nutrients have resulted in decrease in DO concentrations along the river. With the objective of modeling of the water quality of the river a one- dimensional river and stream water quality model QUAL2Kw was calibrated and confirmed using the data for the period of 2012-13. With some exceptions it represented the collected data quite good. Simulation of various water quality constituents was done applying the model during dry and wet season. The result shows that the DO concentration was very low in all parts of the river. BOD and COD was very high compare to standard level of Malaysia. Due to industrial wastewater the pollution was high and without taking improve management based on the simulated results, the scenario will not change.